Reasons for students' poor clinical competencies in the Primary Health Care: Clinical nursing, diagnosis treatment and care programme - Nomasonto B. Magobe; Sonya Beukes; Ann Müller (AOSIS, 2010)
'No member of [health] staff should undertake tasks unless they are competent to do so' is stated in the Comprehensive Primary Health Care Service Package for South Africa (Department of Health 2001)document. In South Africa, primary clinical nurses (PCNs), traditionally known as primary health care nurses (PHCNs), function as 'frontline providers' of clinical primary health care (PHC) services within public PHC facilities, which is their extended role. This extended role of registered nurses(set out in section 38A of the Nursing Act 50 of 1978, as amended) demands high clinical competency training by nursing schools and universities. The objectives of the study were to explore and describe the perceptions of both clinical instructors and students, in terms of the reasons for poor clinical competencies. Results established that two main challenges contributed to students' poor clinical competencies: challenges within the PHC clinical field and challenges within the learning programme (University). Opsomming Die primêre kliniese verpleegkundiges, tradisioneel bekend as primêre gesondheidsorg verpleegkundiges, funksioneer in Suid-Afrika as eerste-linie verskaffers van kliniese primêre gesondheidsorg (PGS) dienste binne die publieke PGS fasiliteite. Dit is hulle uitgebreide rol. Hierdie uitgebreide rol van die verpleegkundige (soos deur Wet op Verpleging,No 50 van 1978, artikel 38A voorgeskryf), vereis opleiding in kliniese vaardighede van hoë gehalte deur verpleegskole en universiteite. Die doelwitte van die navorsing was om die persepsies van beide kliniese dosente en leerders,met betrekking tot die redes vir swak kliniese vaardighede, repektiewelik te verken en te beskryf.Twee temas is deur die resultate as uitdagings (hoof redes) vir die swak vaardighede van leerders aangetoon, naamlik uitdagings in die PGS kliniese praktyk en die uitdagings in die leerprogram (universiteit).